Serum and Extracellular Vesicle MicroRNAs miR-423, miR-199, and miR-93* As Biomarkers for Acute Graft-versus-Host Disease - Crossland, Rachel E.; Norden, Jean; Kralj Juric, Mateja; Pearce, Kim F.; Lendrem, Clare; Bibby, Louis A.; Collin, Matthew; Greinix, Hildegard T.; Dickinson, Anne M. (Frontiers in Immunology, 2017)
Acute graft-versus-host disease (aGvHD) is a major cause of adverse outcome in hematopoietic stem cell transplantation (HSCT), with a high incidence (20-50%). A novel, non-invasive diagnostic test to predict for prevalence and severity would enable improved prophylaxis and reduce morbidity. Circulatory microRNAs miR-423, miR-199, miR-93* and miR-377 have previously been associated with aGvHD in post-HSCT patient plasma, but validation is lacking and their expression within extracellular vesicles (EVs) has not been explored. This study replicated elevated serum expression of miR-423 (p<0.001), miR-199 (p=0.04), miR-93* (p<0.001) and miR-377 (p=0.03) in aGvHD, using a prognostic cohort of day 14 (D14) post-HSCT patient samples (n=81). Expression also associated with disease severity. Further analysis at aGvHD diagnosis in an independent cohort (n=65) confirmed high miR-423 (p=0.02), miR-199 (p=0.007) and miR-93* (p=0.004) expression at disease onset. Investigation of expression patterns during early HSCT sequential timepoints (pre-HSCT to D28) identified elevated microRNAs at D7 post-HSCT in all transplant patients. In a novel investigation of microRNA expression in serum EVs (n=15), miR-423 (p=0.09), miR-199 (p=0.008) and miR-93* (p=0.001) levels were lower at D14 in patients who later developed aGvHD, and this was replicated for miR-423 (p=0.02) and miR-199 (p=0.04) (n=47). Comparing serum to circulating EVs, at D14 patients remaining aGvHD-free had higher expression of miR-423 (p=0.03), miR-199 (p<0.001) and miR-93* (p=0.001) in the EV fraction. Results verify the capacity for circulating miR-423, miR-199 and miR-93* as diagnostic and prognostic aGvHD biomarkers. The novel finding of their differential expression in EVs suggests a potential role in aGvHD etiology.